Pengaruh Online Customer Review dan Customer Satisfaction terhadap Repurchase Intention pada Produk Fashion Erigo di Shopee - Siska Hadiyanti; Ninggar Agustina Cindya Putri; Elan Rusnendar; Andriya Risdwiyanto; Okta Eka Putra (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study examines the influence of online customer reviews and customer satisfaction on repurchase intention for Erigo fashion products sold on Shopee. The research is motivated by the rapid growth of local fashion sales on e-commerce platforms, yet the Erigo brand shows relatively low repurchase intention despite receiving many positive ratings. This gap between consumer expectations and actual experiences highlights the importance of satisfaction in driving loyalty. The study adopts a quantitative approach with descriptive and verificative methods. The population consists of Shopee consumers who have purchased Erigo products, with purposive sampling applied. A total of 362 valid responses were analyzed after outlier removal from 385 initial respondents. Descriptive results indicate that online customer reviews are categorized as very high (4.40), customer satisfaction as high (4.08), and repurchase intention as good (3.95). The findings show that online customer reviews contribute 47.70%, customer satisfaction 57.10%, and both variables jointly 59.60% to repurchase intention. Hypothesis testing confirms significant partial and simultaneous effects of both predictors on repurchase intention.